2015
DOI: 10.1016/j.clinbiomech.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular cartilage defects cause altered hip and knee joint coordination variability during gait

Abstract: Background Patients with acetabular cartilage defects reported increased pain and disability compared to those without acetabular cartilage defects. The specific effects of acetabular cartilage defects on lower extremity coordination patterns are unclear. The purpose of this study was to determine hip and knee joint coordination variability during gait in those with and without acetabular cartilage defects. Methods A combined approach, consisting of a semi-quantitative MRI-based quantification method and vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…Subjects in subnetwork 2 ambulated with a more extended knee joint compared to the rest of the network and may potentially affect hip joint mechanics as well. Although we did not observe any differences in hip joint mechanics between subnetwork 2 and the rest of the cohort, previous work has shown reduced peak hip extension and external hip flexion moment in subjects with hip OA and suggests sagittal plane hip joint mechanics may be an important factor in disease progression. Similar to the results of our study, previous work has demonstrated reduced knee joint excursions in patients with hip OA.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…Subjects in subnetwork 2 ambulated with a more extended knee joint compared to the rest of the network and may potentially affect hip joint mechanics as well. Although we did not observe any differences in hip joint mechanics between subnetwork 2 and the rest of the cohort, previous work has shown reduced peak hip extension and external hip flexion moment in subjects with hip OA and suggests sagittal plane hip joint mechanics may be an important factor in disease progression. Similar to the results of our study, previous work has demonstrated reduced knee joint excursions in patients with hip OA.…”
Section: Discussioncontrasting
confidence: 86%
“…Biomechanical data acquisition used in this study is similar to previous work and is briefly described below. A 10‐camera motion capture system (VICON, Oxford Metrics, Oxford, UK) was used to obtain 3D position data at a sampling rate of 250 Hz, while ground reaction forces (GRFs) were obtained simultaneously using two embedded force platforms (AMTI, Watertown, MA) at a sampling rate of 1000 Hz.…”
Section: Theory and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All raw marker position and ground-reaction force data were filtered using a fourth-order Butterworth filter at 6 Hz and 50 Hz, respectively. 28 The standing calibration trial was used to create a 7-segment kinematic model consisting of the pelvis, bilateral thighs, shanks, and feet in Visual3D (v5.00.16; C-Motion). Local joint coordinate systems were created, and an unweighted least squares method was used to describe segment position and orientation.…”
Section: Methodsmentioning
confidence: 99%